A Critical Study of The Arabic Dictionary: Al-Wasith Dictionary - Hadziq, Muhammad Fadhil; Makfiro, Nikmatul; Fithtriyah, Aidah; Bahruddin, Uril (Al-Manar, 2024)
Dictionaries plays a significant role as the repository of language, preserving the culture and civilization of peoples through examples and evidence within it. It proves to be an effective tool for learning the Arabic language, especially for non-native speakers. This research Dictionaries come in various forms. They can be categorized based on the number of languages involved: monolingual and bilingual or multilingual. One prominent monolingual Arabic dictionary is the "Al-Wasith Dictionary" issued by Academy of the Arabic Language in Cairo. This research aims to critically study this dictionary, including an introduction to Academy of the Arabic Language, its achievements, and the methodology of compiling the dictionary. Additionally, this research seeks to analyze the advantages and disadvantages encountered by Arabic language learners during their use of this dictionary, ultimately proposing suggestions or remedies to enhance and improve it.